„Pokrzywione bemole” — o inspiracjach muzycznych w twórczości poetyckiej Brunona Jasieńskiego (jak również o autorach, dla których twórczość ta stała się muzyczną inspiracją) słów kilka - Jaworski, Krzysztof (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2012)
The article describes the importance of public performance for the image of the Futurists, mainly of Bruno Jasieński. The impressions that the artists gained from Helena Buczyńska’s ‘word-arts’ performance, and Scriabin’s idea of ‘Art Religion’ they were exposed to, inspired the young poets. The article finishes with enumeration of several inspirations that are being found in Jasieński’s texts by modern musicians adapting his poetry.